Concomitant Usage of H1‐Antihistamines and Immune Checkpoint Inhibitors on Cancer Patient Survival - Yin Leung; Terry Cheuk‐Fung Yip; Grace Lai‐Hung Wong; Vincent Wai‐Sun Wong; Vicki Wing‐Ki Hui; Tony Shu‐Kam Mok; Henry Lik‐Yuen Chan; Stephen Lam Chan; Rashid Nok‐Shun Lui (Cancer Medicine)
ABSTRACT Purpose Recent research (Li et al. 2021) suggests an upregulated expression and activation of H1 receptors on macrophages in the tumor microenvironment, and concomitant H1‐antihistamine use is associated with improved overall survival in patients with lung and skin cancers receiving immunotherapy. Therefore, we retrospectively evaluated the impacts of H1‐antihistamine use in cancer patients during immunotherapy. Methods All patients who had received at least one dose of immune checkpoint inhibitors (ICIs) from July 1, 2014 to October 31, 2019 were identified from Hong Kong's territory‐wide database, with this date defined as the baseline. A 1‐month landmark analysis was conducted with follow–for up to 6 months, including an exposure period of 1 month before and after the baseline date. Patients were grouped according to the types of primary cancer and the percentages of daily H1‐antihistamine usage within the exposure period. The primary outcome was overall survival. Results A total of 1740 (65.1% male, mean age 61.9 years) were included in the landmark analysis, of which 529 (30.4%) and 307 (17.6%) had primary lung and liver malignancies. The multivariable Cox regression model estimated statistically significant improvement in overall survival of intermediate use in patients with primary lung malignancies (adjusted hazard ratio [aHR] 0.223, 95% confidence interval [CI] 0.052–0.958, p = 0.044), but not with primary liver maligancies. Similar frequency‐dependent effects were identified in Kaplan–Meier analysis. Conclusion The benefits of adjunctive use of H1‐antihistamines may be generation‐ and tumor‐dependent. Further clinical and mechanistic studies are required to confirm the findings.